(untitled) (Reflection and Critique Law Magazine, 2022)
This article analyses the phenomenon of virtual assets considering the institution of legal rules to govern the circulation of cryptoassets and fight all illegal activities related to them. Thus, we describe the mechanisms of its operation and the emerging problems of legal nature, considering that global digitization requests new requirements, without which it will not be possible to achieve an adequate legal regulation to the digital age. The research is based on the analytical method and was carried on literary and normative sources. The novelty of this study is due to the need to converge the legal and information systems to the fast digitalization process in society. In this sense, it is clear that the lack of legal regulation and technical resources make the new digital solutions attractive to illegal activities and requesting more time to solve the legal regulation issues, more risks of use of virtual assets will be aggravated.